City market: sustainable urban lifestyle hub in Johannesburg - Mela, Claudia (My University, 2011)
The essence and feeling of any city around the world may be experienced by discovering the local markets and exploring the cities rich histories, food and culture. Johannesburg is unique in the way traders have adapted to the ever changing social and political situation of our country. This thesis will deconstruct the new era of markets, revealing the very social and political issues that consume and surround them. Exploration of the topic will initiate by understanding the historical context and learning from the contemporary trading system in order to ultimately plan a contemporary market set within a historical environment. Explorations of markets and trading within the Gauteng region will reveal the divide that occurs between the various trading typologies and the effect it has on our society. Through rethinking spatial environments the contemporary market has the potential for narrowing the cultural divide, providing new systems and spaces for public interaction and revitalising the urban environment. Research will reveal the important role markets play in the lives of people and the importance of the need to provide fresh products and revitalise the urban framework in order to enhance a healthier lifestyle. Evidence based design research will provide the tools and contribute to the architectural response of the topic and the creation of the proposed market intervention which aims at creating a dynamic hybrid that captures the authenticity of our food and market culture